Developing my theory of practice as a teacher-researcher through a case-study of CLIL classroom interaction - Wiesemes, Rolf (2002)
Research by the Nuffield Foundation (2000) suggests that the teaching and learning of Modern Foreign Languages (MFL) in English secondary schools is in crisis. At the same time, some schools are implementing initiatives intended to raise the status and the quality of MFL learning.